Impact of behavioural factors on sustainable fashion usage intention: Evidence from consumers in Ho Chi Minh City (International Journal of Scientific Research and Management (IJSRM), 2023)
This study quantifies the impact of behavioral factors on sustainable fashion usage intention using self-reported data of 396 consumers in Ho Chi Minh City 2023. Sustainable fashion usage intention is measured using five factors based on behavioral theory and qualitative research 1) Attitude, 2) Social value, 3) Perceived behavioral control, 4) Subjective norms, and 5) Sustainable clothing disposal. We examine the cognitive processes of sustainable fashion consumers as they made usage decisions, as well as the subsequent implications of their choices. The results suggest that sustainable fashion usage intention is impacted by two characteristics influencing young generation intention in sustainable fashion in HCMC: Attitude and social value.